THE USE OF VIDEO IN TEACHING WRITING OF DESCRIPTIVE TEXT FOR THE TENTH GRADE STUDENTS AT SMA NEGERI 1 STABAT - Mellya Miranda Putri; Berlin Sibarani (Universitas Negeri Medan, 2022)
The aim of this study was to describe the use of video and analyze the reasons ofusing video in teaching and learning process especially in writing descriptive textfor tenth grade students at SMA Negeri 1 Stabat. This study was qualitativelyconducted that taken two english teachers of SMA Negeri 1 Stabat. The data werecollected by using recording, depth interview and observing the whole processesof teaching writing descriptive text. The findings of this study showed that theteacher 1 only used four ways from seven ways while the teacher 2 only usedthree ways from seven ways. The researcher used Berk theory in analyzing theteachers’ ways in using video in teaching descriptive text. There were reasons ofusing video in teaching and learning process that had gotten from teachers’interview. Then based on the data, the reasons dominantly were see and also hearthe language in use, be more active, creative, attractive, motivated, enjoyable, andthe important things by the video the student could master the material in goodenough. The findings of this study revealed that video contributed to the study offoreign language teaching especially teaching writing.